2022
DOI: 10.1002/wrna.1705
|View full text |Cite
|
Sign up to set email alerts
|

PINTology: A short history of the lncRNA LINC‐PINT in different diseases

Abstract: LINC-PINT is a p53-induced long intergenic noncoding transcript that plays a crucial role in many diseases, especially cancer. This long noncoding RNA (lncRNA) gene produces in total 102 (LNCipedia) alternatively spliced variants (LINC-PINT:1 to LINC-PINT:102). The functions of known variants include RNA transcripts, host transcripts for circular RNA (circRNA) generation and as sources for the translation of short peptides. In most human tumors, LINC-PINT is down-regulated where it serves as a tumor suppressor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 169 publications
0
10
0
Order By: Relevance
“…As such, their expression and function are often altered in disease states (Kleinbrink et al, 2021;Yang et al, 2021;Anderson and Anderson, 2022;Dietlein et al, 2022;Erdogan et al, 2022) with selected examples now being used as diagnostic markers for various diseases including cancers (Li et al, 2019;Deng and Zou, 2022;Najafi et al, 2022;Zhang et al, 2022). Among these, one particular lncRNA called LINC-PINT (P53 Induced long Non-coding Transcript) appears exceptional because of its universalized functions and relationship to the famous tumor suppressor gene P53 (He et al, 2021;Bukhari et al, 2022). Indeed, like P53, LINC-PINT was first proposed as an oncogene but later revealed as a tumor suppressor in human cancers.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…As such, their expression and function are often altered in disease states (Kleinbrink et al, 2021;Yang et al, 2021;Anderson and Anderson, 2022;Dietlein et al, 2022;Erdogan et al, 2022) with selected examples now being used as diagnostic markers for various diseases including cancers (Li et al, 2019;Deng and Zou, 2022;Najafi et al, 2022;Zhang et al, 2022). Among these, one particular lncRNA called LINC-PINT (P53 Induced long Non-coding Transcript) appears exceptional because of its universalized functions and relationship to the famous tumor suppressor gene P53 (He et al, 2021;Bukhari et al, 2022). Indeed, like P53, LINC-PINT was first proposed as an oncogene but later revealed as a tumor suppressor in human cancers.…”
Section: Introductionmentioning
confidence: 99%
“…LINC-PINT contributes to a variety of biological processes impacting cancer cell growth and metastasis, with involvement in processes ranging from DNA damage responses to cell senescence and apoptosis (Simchovitz et al, 2020;He et al, 2021;Wang et al, 2021;Xiang et al, 2021;Zhang et al, 2021;Bukhari et al, 2022). It has also been shown to be an essential regulator of many other diseases, including autoimmune diseases (Wang and Zhao, 2020;Salviano-Silva et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have reported that the lncRNA, p53-induced transcript (LINC-PINT) is downregulated in several cancer types, including colon cancer, lung cancer, breast cancer, glioblastoma, and GC ( Marin-Bejar et al, 2013 ; Marin-Bejar et al, 2017 ; He et al, 2021 ; Bukhari et al, 2022 ). LINC-PINT directly interacts with the polycomb repressive complex 2 (PRC2) to regulate the expression of downstream genes ( Marin-Bejar et al, 2013 ; Marin-Bejar et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%